Improvement Of The System Of Formation And Development Of Creative Activity Of Future Educators On The Basis Of PersonalityOriented Education - Rakhimova Feruzakhon Muhammadjonovna (Genius Journals, 2021)
Modern pedagogical technologies are now becoming a necessary and basic component of the educational process for a preschool institution. It is considered important that educators who provide education and training in pre – school educational institutions have comprehensive knowledge and spirituality. The reason is that children take an example by looking at them. In addition, the need for the use of advanced pedagogical technologies in the formation of their cognitive skills and creative activities indicates that the effectiveness of interactive methods is significant in the acquisition of the necessary knowledge and skills. Education motivation plays an important role in the organization of educational activities. It helps to fawn, to walk in a critical manner. In this article, information on the improvement of the system of formation and development of creative activities of future educators on the basis of personality-oriented education will be collected and reviewed.
Keywords: Person-oriented education; preschool; future educator; system of development